In Vitro Evaluation of Calcium Phosphate Bone Cement Composite Hydrogel Beads of Cross-Linked Gelatin-Alginate with Gentamicin-Impregnated Porous Scaffold - Shih-Ming Liu; Wen-Cheng Chen; Chia-Ling Ko; Hsu-Ting Chang; Ya-Shun Chen; Ssu-Meng Haung; Kai-Chi Chang; Jian-Chih Chen (MDPI AG, 2021)
Calcium phosphate bone cement (CPC) is in the form of a paste, and its special advantage is that it can repair small and complex bone defects. In the case of open wounds, tissue debridement is necessary before tissue repair and the subsequent control of wound infection; therefore, CPC composite hydrogel beads containing antibiotics provide an excellent option to fill bone defects and deliver antibiotics locally for a long period. In this study, CPC was composited with the millimeter-sized spherical beads of cross-linked gelatin-alginate hydrogels at the different ratios of 0 (control), 12.5, 25, and 50 vol.%. The hydrogel was impregnated with gentamicin and characterized before compositing with CPC. The physicochemical properties, gentamicin release, antibacterial activity, biocompatibility, and mineralization of the CPC/hydrogel composites were characterized. The compressive strength of the CPC/hydrogel composites gradually decreased as the hydrogel content increased, and the compressive strength of composites containing gentamicin had the largest decrease. The working time and setting time of each group can be adjusted to 8 and 16 min, respectively, using a hardening solution to make the composite suitable for clinical use. The release of gentamicin before the hydrogel beads was composited with CPC varied greatly with immersion time. However, a stable controlled release effect was obtained in the CPC/gentamicin-impregnated hydrogel composite. The 50 vol.% hydrogel/CPC composite had the best antibacterial effect and no cytotoxicity but had reduced cell mineralization. Therefore, the optimal hydrogel beads content can be 25 vol.% to obtain a CPC/gentamicin-impregnated hydrogel composite with adequate strength, antibacterial activity, and bio-reactivity. This CPC/hydrogel containing gentamicin is expected to be used in clinical surgery in the future to accelerate bone regeneration and prevent prosthesis infection after surgery.